TEACHING OF ENGLISH LANGUAGE IN PRESCHOOL EDUCATIONAL INSTITUTIONS - Radjabova Gulchiroy Gayrat kizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: this article describes the methods of teaching English in the preschool education system, and now English is becoming a world language, so it should be started from preschool, i.e. kindergarten, the article provides information about this.